2022
DOI: 10.1002/ejp.2054
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of cannabinoids to Danish patients with treatment refractory chronic pain—A retrospective observational real‐world study

Abstract: Background: Cannabinoids are considered a therapeutic option to patients suffering from treatment refractory chronic pain (TRCP) insufficiently relieved by conventional analgesics or experiencing intolerable adverse events (AEs) from those. This study aimed to explore safety and effectiveness of oral cannabinoids among patients with TRCP.Methods: A retrospective study was conducted among Danish patients with TRCP being prescribed oral cannabinoids. Data on AEs and changes in pain intensity by numeric rating sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…The percentage of patients achieving 30% pain relief in the Horsted et al (2022) study, which ranges between 32%-45% in the PP analysis and 10-17% in the ITT, seems congruent with previous reports. For example, Bialas et al (2022) reported of 38.3% of patients achieving the 30% target in all six included studies, and 20.5% after removing four studies for which an imputation method was used to calculate responder rates.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…The percentage of patients achieving 30% pain relief in the Horsted et al (2022) study, which ranges between 32%-45% in the PP analysis and 10-17% in the ITT, seems congruent with previous reports. For example, Bialas et al (2022) reported of 38.3% of patients achieving the 30% target in all six included studies, and 20.5% after removing four studies for which an imputation method was used to calculate responder rates.…”
supporting
confidence: 91%
“…The same is probably true for the improvement in secondary outcomes such as sleep and quality‐of‐life, and for the rates and types of reported adverse events. Hence, the authors concluded that ‘oral cannabinoid therapy seems to be safe and mildly effective in patients with chronic pain’ (Horsted et al, 2022 ) may strengthen what is already known, but is marginal in terms of added value. An additional major drawback of this and most other real‐world observational studies is their low patient retention rate (26% in the second follow‐up in this study), which creates a significant bias and makes the results difficult to interpret.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The recently published exploratory, non‐controlled, study by Horsted et al (2023) reports on the potential safety and pain‐relieving effects of cannabinoids (THC, CBD), or mixed in a non‐randomized order. The authors conclude that ‘oral cannabinoid therapy in general appears to be safe and effective for relief of chronic pain in some patients, including a subset of patients with cancer‐related pain (9%), not responding adequately to conventional treatment regimens or experiencing intolerable adverse events’.…”
mentioning
confidence: 99%